The Leadership of Prophet Muhammad: A Role Model of Politics and Ethics in the Modern Era - Rifal Saefudin; Ahmad Maftuh Sujana; Dini Handayani; Nurelizah Nurelizah; Muhammad Azka Nabhan (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The leadership of Prophet Muhammad SAW is a perfect illustration of how to harmoniously blend political, moral, and spiritual strength. In addition to guiding the community in religious matters, the Prophet organized social, economic, and political life in accordance with divine principles. His values as a leader justice, integrity, accountability, and consultation demonstrate that power should be used to serve, not to control. This article discusses the leadership of Prophet Muhammad SAW as a moral and political example that remains relevant today. The Prophet was known as a statesman who successfully created a moral and just society, as well as a spiritual leader. His moral and ethical leadership was based on fundamental leadership values including social responsibility, justice, consideration, and honesty. By applying a historical perspective and examining prophetic values, this article demonstrates how the Prophet's teachings on leadership can address various contemporary issues, including declining integrity, abuse of power, and the rise of individualism. The application of these principles will result in leadership that is humane, honest, and focused on society. The leadership of Prophet Muhammad SAW emphasized the use of authority to advance and protect justice rather than to suppress or control. These principles serve as important guidance for leaders in our century to create moral, open governance that supports truth while upholding human and spiritual values